Implications of Government Policy on Investment and Economic Growth - Hendri Khuan; Safiullah Aziz; Amir Raza (Yayasan Adra Karima Hubbi, 2025)
Background. Government policies play a significant role in shaping the investment climate and, consequently, in driving economic growth. Policies aimed at stimulating investments such as fiscal incentives, tax policies, and infrastructure development can significantly influence the flow of capital into various sectors, fostering economic activity and job creation. Objective. This study aims to evaluate the impact of government policies on investment decisions and their subsequent effect on economic growth. The research seeks to identify the key policy factors that drive or hinder investment flows and assess their broader implications for long-term economic performance. Method. A mixed-methods approach was employed, utilizing quantitative data analysis of economic indicators and investment flows from government reports, along with qualitative interviews from business leaders and policymakers. The study examines a range of countries with varying policy environments to identify common trends and impacts. Results. The findings suggest that pro-investment policies significantly boost both domestic and foreign investment, leading to higher economic growth rates. In contrast, restrictive policies and regulatory uncertainties were found to negatively impact economic performance. Conclusion. The study concludes that effective government policies are essential for fostering investment and driving sustainable economic growth. Policymakers should prioritize creating stable, investment-friendly environments to achieve long-term economic benefits.